Analisis Penerapan Prinsip Keadilan Restoratif Pada Anak Pelaku Tindak Pidana Perjudian - Halimah Humayrah Tuanaya; Nursolihi Insani; Ari Widianti (Program Studi Hukum Universitas Pamulang, 2021)
Gambling is a crime whose form of action is mostly wrapped in the form of games, so it is easy to lure children to fall into a criminal consequence. Gambling is basically a victimless crime, so to reach a diversion agreement, it does not require the consent of the victim or the parents of the guardian/victim. If implemented consistently, this will provide a great opportunity for children who are perpetrators of gambling crimes to produce diversion agreements and prevent children from coming into contact with the criminal justice process. This is in line with restorative justice which is the legal goal of the juvenile criminal justice system. The problem in this study is to further examine the application of the principle of restorative justice by elements of the criminal justice system in dealing with children who are perpetrators of gambling crimes. The type of legal research conducted is normative juridical. The problem approach used in this research is an analytical approach. The data used in this study is secondary data. The legal analysis carried out is expected to be able to provide juridical arguments against several decisions related to the problems that are the object of this research. Of the three cases of child gambling examined in this study, it shows that there is a uniformity of approach taken by elements of the criminal justice system in dealing with child gambling offenders. Both investigators, public prosecutors, and judges are still ignorant of the diversion rights that have been regulated in the SPPA Law. As a result, children must come into contact with criminal justice processes that should be avoided in the best interests of children. After the Constitutional Court Decision stating that Articles 96, 99, 100, and 101 of the law no. 11 of 2012 concerning the juvenile criminal justice system are contrary to the constitution, it is necessary to create a control mechanism that is able to maintain the performance of elements in the juvenile criminal justice system in accordance with the objectives of the juvenile criminal justice system which prioritizes restorative justice.